Exploring internal communication : towards informed employee voice - Ruck, Kevin (London ; New York : Routledge, 2020)
'Exploring Internal Communication has long been the go-to publication for internal communication, public relations and human resources practitioners who want their practice to be grounded in research and guided by evidence-based advice. The new fourth edition has been comprehensively updated throughout to reflect the latest practices in internal communication. Notably, the use of social media within organisations is covered in recognition of the increasing integration of digital platforms such as Workplace by Facebook, Slack and Yammer. A greater understanding of the different communication roles played by line managers and senior managers is emerging, and this is explored to help those managers understand what is expected of them and how to succeed as they communicate within this changing environment. And, the demands of channel management are becoming increasingly complex; this edition helps practitioners negotiate this complexity. Enriched with models, tips and case studies, this book is an indispensable tool for both students and practitioners alike'--
Previous edition entered under: Author Kevin Ruck.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Communication in personnel management; Communication in management